Prospecção bioquímica e molecular de fatores possivelmente envolvidos na defesa de feijão-de-corda [Vigna unguiculata (L.) Walp] ao vírus do mosaico severo do caupi (CPSMV) - Magalhães, Vladimir Gonçalves (2011)
Cowpea [(Vigna unguiculata (L.) Walp.)] has a major socioeconomic importance in Northeastern Brazil. However, its production is low due abiotic and biotic factors. Amongst the biotic factors the cowpea severe mosaic virus (CPSMV, Secoviridae family) has a great importance because it causes the most prevalent and serious virus disease that affects this crop in the country. Although there are resistant cultivars to CPSMV, the defense mechanisms involved is not understood. For this reason, a comparative study was conducted between resistant and susceptible cultivars, using two experimental approaches. In the first one, the biochemical approach, possible differences of enzyme activities related to oxidative stress (superoxide dismutase, ascorbate peroxidase, guaiacol peroxidase) and pathogenesis (β-1,3-glucanase and chitinase), in addition of phenyl amonium lyase, and H2O2 generation in the leaves of the cultivars Pitíuba (susceptible) and Macaibo (resistant) were analyzed. The secondary leaves were harvested at 6, 12, 24, 48, 72 h after treatment with CPSMV or carborundum (controls) and these above parameters were measures in the protein extracts obtained. It was shown that, in general, the response amongst the cultivars did not differ significantly, suggesting that the defense mechanisms of cowpea are different from the classic response of defense observed for several plant species. In the second approach, molecular, the nucleotide sequences of the genes that code for the translation initiation factors (eIF4E, eIF(iso)4E, eIF4G, eIF(iso)4G and nCBP) and the primary strucuture of the correspondent putative proteins were analyzed in order to search patterns of polymorphis between the studied cowpea cultivars that could be related to a constitutive defense conferred by recessive genes. After sequence analysis, it was found that eIF4E showed polymorphisms between cultivars, and, in at least two positions (68 and 108), there were differences between susceptible and resistant cultivars (Arg68/Pro68; Val108 or Pro108/Ala108). The molecular modeling revealed that differences in amino acid are located in two external loops close to the cap (m7G) binding domain, well reported in cases of recessive resistance within the Potyviridae family. Through immunodetection studies with the leaf extracts and the protein fractions obtained after the affinity chromatography on a Sepharose-7-metil-guanosina column, it was found that the amino acid mutations found did not impair the ability of eIF4E to bind to M7G in vitro. However, as it was observed two variants for eIF4E comparing the resistant and susceptible cultivars to CPSMV, at spatially neighboring regions, it could not be ruled out the hypothesis that this constitutive/recessive resistant trait is correlated with these mutations detected, which could impair, consequently, the in vivo interaction of eIF4E with the viral VPg.